Dietary assessment and its awareness in female students from different Health Departments: unhealthy diet with normal BMI - Amani AlHazmi; Farah Aziz (SAGE Publishing, 2020)
Background: Dietary habits are of substantial concern related to the health of college students. Medical students are expected to have better dietary habits and healthy lifestyle, but due to various factors they are least bothered to follow recommended healthy diet. The present study assessed and compared the eating habits, nutritional awareness and BMI in females from health departments of King Khalid University (KKU), Saudi Arabia.  Designs and Methods: The cross-sectional survey was conducted in undergraduate females from eight health departments: Public Health, Nursing, Medical Laboratory Science, Physiotherapy, Medicine and Surgery, Dental and Oral surgery, Diagnostic Radiology and Pharmacy. Participants completed online questionnaire that include demographic, anthropometric information, questions related to food preference and nutritional awareness. BMI, food preferences, and nutritional awareness responses were assessed and compared among different departments at 0.05 and 0.001 level of significance. Results: Total of 377 females were analysed and the mean BMI differ significantly at p<0.05 in all departments reporting the highest BMI mean in medicine and surgery department. Upon further stratification of BMI 53% of total analysed students comes under normal BMI. The utmost frequency of overweight students (55.3%) were observed in physiotherapy with no obese category followed by nursing with least obese students (2.2%). Conclusions: Inadequate food preference with unhealthy dietary habits but satisfactory nutritional awareness was observed in students of all departments with no significant difference. Designing of nutrition promotional programs and motivation is required for the acquisition of healthy dietary habits.